Faecal microbiota transplant ameliorates gut dysbiosis and cognitive deficits in Huntington's disease mice. Issue 4 (12th August 2022) - Gubert, Carolina; Choo, Jocelyn M; Love, Chloe J; Kodikara, Saritha; Masson, Bethany A; Liew, Jamie J M; Wang, Yiwen; Kong, Geraldine; Narayana, Vinod K; Renoir, Thibault; Lê Cao, Kim Anh; Rogers, Geraint B; et al.
Abstract: Huntington's disease is a neurodegenerative disorder involving psychiatric, cognitive and motor symptoms. Huntington's disease is caused by a tandem-repeat expansion in the huntingtin gene, which is widely expressed throughout the brain and body, including the gastrointestinal system. There are currently no effective disease-modifying treatments available for this fatal disorder. Despite recent evidence of gut microbiome disruption in preclinical and clinical Huntington's disease, its potential as a target for therapeutic interventions has not been explored. The microbiota–gut–brain axis provides a potential pathway through which changes in the gut could modulate brain function, including cognition. We now show that faecal microbiota transplant (FMT) from wild-type into Huntington's disease mice positively modulates cognitive outcomes, particularly in females. In Huntington's disease male mice, we revealed an inefficiency of FMT engraftment, which is potentially due to the more pronounced changes in the structure, composition and instability of the gut microbial community, and the imbalance in acetate and gut immune profiles found in these mice. This study demonstrates a role for gut microbiome modulation in ameliorating cognitive deficits modelling dementia in Huntington's disease. Our findings pave the way for the development of future therapeutic approaches, including FMT and other forms of gut microbiome modulation, as potential clinical interventions for Huntington's disease. Abstract : Gubert et al. report that faecal microbiota transplant from wild-type into Huntington's disease mice positively modulates cognitive outcomes, particularly in females. They demonstrate sexually dimorphic and progressive gut dysfunction, and microbial disruption, and provide the first evidence supporting microbiota manipulation as a therapeutic intervention for Huntington's disease, particularly cognitive symptoms. Graphical Abstract: Graphical abstract